2015
DOI: 10.1353/pla.2015.0026
|View full text |Cite
|
Sign up to set email alerts
|

University Rankings: How Well Do They Measure Library Service Quality?

Abstract: University rankings play an increasingly large role in shaping the goals of academic institutions and departments, while removing universities themselves from the evaluation process. This study compares the library-related results of two university ranking publications with scores on the LibQUAL+™ survey to identify if library service quality-as measured within the LibQUAL+™ dimensions affect of service, information control, and library as place-is related to the standings. The results suggest that some indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…LibQUAL is a recognized tool for the measurement of user's perceptions and expectations regarding LSQ in three domains: “Effect of service” (ES), “information control” (IC) and “library as a place” (LP) (Cook et al , 2003, 2008, 2009, 2010). “LibQUAL + TM scores are representative of library service quality, as judged by the users, and may be validly used as the measure of such for comparative purposes” (Jackson, 2015, p. 318). Kyrillidou (2011) reported in 2011 that twelve hundred libraries had surveyed more than 1.5 million of users using LibQUAL + since its inception.…”
Section: Development Of Libqual Instrumentmentioning
confidence: 99%
“…LibQUAL is a recognized tool for the measurement of user's perceptions and expectations regarding LSQ in three domains: “Effect of service” (ES), “information control” (IC) and “library as a place” (LP) (Cook et al , 2003, 2008, 2009, 2010). “LibQUAL + TM scores are representative of library service quality, as judged by the users, and may be validly used as the measure of such for comparative purposes” (Jackson, 2015, p. 318). Kyrillidou (2011) reported in 2011 that twelve hundred libraries had surveyed more than 1.5 million of users using LibQUAL + since its inception.…”
Section: Development Of Libqual Instrumentmentioning
confidence: 99%
“…Academic libraries play a key role in this context (Hernon and Schwartz, 2015; Jackson, 2015; Jantz, 2017) by delivering educational and research services to the academic community, helping to improve productivity and even promoting university rankings. Thus, libraries, by properly utilizing IT and its potentials, can help to increase innovation to improve knowledge services and gain the competitive advantage of complying with the goals of a university (Heinrichs and Lim, 2009; Jantz, 2012b).…”
Section: Problem Statementmentioning
confidence: 99%
“…University's rankings are very crucial for the nation building and there was one study describing that the 'library as place' dimension has the strongest and most consistent relationship with the rankings. Librarian and other stakeholders must understand and focus on library's contribution with the university rankings (Jackson, 2015). At the University of Limerick (UL) Library, Ireland, the author has conducted a survey for the past 5 years LibQUAL+ data of 2007, 2009, 2012, 2014 and 2016. The results revealed that user perceptions of library services steadily improved, and users are much more satisfied in 2016 than they were in 2007, with the overall library services.…”
Section: Emerging Patterns and Trends Reflected On Lsq Studiesmentioning
confidence: 99%